Landmine detection technologies to face the demining problem in antioquia (2014)
This paper presents a review of existing landmine detection techniques. The review is made with an analysis of the strengths and weaknesses of each technique in relation to the landmine detection problem in Antioquia, which ranks first in Colombia by the number of victims from landmines. According to the uniqueness of landmines and terrains in Antioquia, this paper suggests some research topics that may help in the demining task for this affected department.